Anti-thrombotic Mechanisms of Echinochrome A on Arterial Thrombosis in Rats: In-silico, In-vitro and In-vivo Studies - Khalaf, Marina Lotfy; Soliman, Amel Mahmoud; Fahmy, Sohair Ramadan; Mohamed, Ayman Saber (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2025)
Background Arterial thrombosis is one of the most significant healthcare concerns in the world. Echinochrome A (Ech-A) is a natural quinone pigment isolated from sea urchins. It has a variety of medicinal values associated with its antioxidant, anticancer, antiviral, anti-diabetic, and cardio-protective activities. Objectives The current study aims to investigate the effect and mechanism of Ech-A to inhibit thrombus formation induced by ferric chloride in rats. Methods Twenty-four rats were assigned into four groups (n= 6); sham and thrombotic model groups were orally administered 2% DMSO, while the other groups were treated with two dosages of Ech-A (1 and 10 mg/kg, body weight). After seven days of administration, all groups were exposed to 50% ferric chloride for 10 min, except the sham group exposure to normal saline. Results The molecular docking showed the free binding energies of Ech-A and vitamin K (Vit. K) with Vit. K epoxide reductase were -8.5 and -9.8 kcal/mol, which confirm the antithrombotic activity of Ech-A. The oral administration of Ech-A caused a significant increase in partial thromboplastin time, prothrombin time, clotting time, platelet count, fibrinogen levels, factor VIII, glutathione reduced, catalase, nitric oxide, and glutathione S-transferase. While white blood cells count, calcium level, and malondialdehyde concentration significantly decreased. The histological examination revealed a definite improvement in the carotid and cardiac tissues in the Ech-A groups. Conclusion The study results showed that Ech-A prevented thrombosis by several mechanisms, including chelating calcium ions, increasing the NO concentration, suppressing oxidative stress, and antagonizing Vit. K.
Keywords: ferric chloride